A Detailed Look at Accuracy‐Related Penalties. Issue 3 (16th February 2018) - Unknown
Abstract : When the dust settled in this case, the petitioners, donors of a conservation easement, were found liable for the 40 percent accuracy‐related penalty for a gross valuation misstatement ( Roth v. Commissioner, US Tax Court, December 28). They claimed a charitable contribution deduction in the amount of 970, 000; the parties settled on a deduction amount of 30, 000. There was agreement that the donors had reasonable cause for the amount of the claimed deduction.